2021
DOI: 10.1080/20009666.2021.1929047
|View full text |Cite
|
Sign up to set email alerts
|

Preferences to improve rounding efficiency amongst hospitalists: a survey analysis

Abstract: Background: There is no 'gold standard' method of rounding for hospitalists. This study investigates hospitalist rounding preferences to improve efficiency based on resources categorized under work assignment and communication. Methods: An anonymous survey containing demographics and questions on preferences for rounding efficiently by hospitalists were widely distributed online. Res6ponses were presented using descriptive statistics and SPSS v26. Results: There were 143 respondents, majority male (60%) with (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…These pages often lack standardization, content, format, urgency level, and clarity within the message. Some studies reported that the medical staff were found to prefer in-person interactions with consults instead of over-the-phone consults or pagers due to a higher level of productive communication, reducing turnaround time by up to 50% [ [29] , [30] , [31] ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These pages often lack standardization, content, format, urgency level, and clarity within the message. Some studies reported that the medical staff were found to prefer in-person interactions with consults instead of over-the-phone consults or pagers due to a higher level of productive communication, reducing turnaround time by up to 50% [ [29] , [30] , [31] ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians also prefer to communicate with the consultant via text or phone more often than face-to-face talk. Unfortunately, while clinicians have technology and resources available, they do not always use them or are not suitable or customised to their use [ 30 , 31 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation